The effect of income and expense shifting on the corporate income tax evasion - Sabina Kołodziej; Ewa Wanda Maruszewska; Małgorzata Niesiobędzka (Central European Management Journal)
Purpose – This paper aims to present a study on the effect of income and expense shifting on the corporate income tax evasion – an example of intentional noncompliance practiced by tax agents. The authors expected that the tool used would differentiate the extent of understatement of tax liability. Design/methodology/approach – Two experiments were conducted in which young (N = 62) and experienced (N = 68) tax agents read a scenario placing them in a position of an employee responsible for tax planning and calculations of tax liabilities. The respondents’ task was to decide about the extent of the tax liability understatement using income or expense shifting. Findings – Research demonstrated significantly higher extent of corporate income tax understatement when using income shifting compared to expense shifting in case of experienced tax agents (Study 2) and on tendency level among young tax agents (Study 1). Research limitations/implications – Results of the studies might be of interest to managers paying attention to tax procedures within the company, governmental agencies investigating corporate tax evasion, as well as educators responsible for tax agents’ initial training and lifelong learning. Originality/value – This study concentrates on tax agents who are employed in companies and corporate income tax evasion, which has not been analyzed in the literature so far.